THE EFFECT OF STORE ATMOSPHERE, MENU VARIETY, AND CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER LOYALTY AT WARUNG SALIRE - Ahmad, Habib (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of store atmosphere, menu variety, and customer relationship management on customer loyalty at Warung Salire Ngagel Surabaya. The research method used is a quantitative approach by distributing questionnaires to 155 respondents. Data analysis techniques include validity testing, reliability testing, classical assumption tests, multiple linear regression, and hypothesis testing both simultaneously and partially. The results show that simultaneously, all three variables significantly influence customer loyalty. Partially, menu variety and customer relationship management have a significant effect, while store atmosphere does not. The conclusion of this study is that attractive menu offerings and effective customer relationship management play a crucial role in enhancing customer loyalty at Warung Salire.